2003
DOI: 10.1366/000370203322005328
|View full text |Cite
|
Sign up to set email alerts
|

Effect on the Partial Least-Squares Prediction of Yarn Properties Combining Raman and Infrared Measurements and Applying Wavelength Selection

Abstract: The combination of Raman and infrared spectroscopy on the one hand and wavelength selection on the other hand is used to improve the partial least-squares (PLS) prediction of seven selected yarn properties. These properties are important for on-line quality control during production. From 71 yarn samples, the Raman and infrared spectra are measured and reference methods are used to determine the selected properties. Making separate PLS models for all yarn properties using the Raman and infrared spectra, prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…A similar observation was reported in Reference [33], where IR and Raman spectroscopic measurements were jointly involved into a regression modeling of yarn properties. In spite of various data pretreatments applied, including variable selection, no improvement of prediction performance with concatenated data compared to individual data blocks had been obtained.…”
Section: Regression Data Analysissupporting
confidence: 78%
“…A similar observation was reported in Reference [33], where IR and Raman spectroscopic measurements were jointly involved into a regression modeling of yarn properties. In spite of various data pretreatments applied, including variable selection, no improvement of prediction performance with concatenated data compared to individual data blocks had been obtained.…”
Section: Regression Data Analysissupporting
confidence: 78%
“…However, the simple addition of any spectroscopic method does not generally result in synergy. For instance, a combination of MIR [ 39 ] or NIR [ 40 ] with Raman spectroscopy did not bring any accuracy gain of the target component determination. At the same time, the latter combination was profitable for another analyte [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alamprese et al, reported minced beef evaluation based on combining UV–vis, NIR, and MIR spectra [ 37 ]. De Groot et al, improved the predicted accuracy of yarn properties based on the combination of selected MIR and Raman spectra [ 38 ].…”
Section: Introductionmentioning
confidence: 99%